Hip Imaging: Normal Variants and Asymptomatic Findings - Omoumi, Patrick; Vande Berg, Bruno (Seminars in Musculoskeletal Radiology, 2017)
With the increasing use of imaging as a diagnostic tool for hip pain, more and more anatomical variants are detected, and more findings are seen in asymptomatic populations, especially in older individuals. The radiologist must be aware of these variants and asymptomatic findings to avoid interpretative errors and overdiagnosis. In this review, we cover frequently encountered anatomical variants and asymptomatic findings that can be found in the bony structures of the hip, the joint itself, as well as in the surrounding soft tissues.
Keywords: hip; joint; MRI; CT; radiography